2020
DOI: 10.3390/polym12102229
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Dimethyl Octyl Aminoethyl Ammonium Bromide and Preparation of Antibacterial ABS Composites for Fused Deposition Modeling

Abstract: Additive manufacturing (AM) demonstrates benefits in the high-precision production of devices with complicated structures, and the modification of materials for AM is an urgent need. To solve the bacterial infection of medical devices in their daily application, dimethyl octyl aminoethyl ammonium bromide (octyl-QDED), an organic antibacterial agent, was synthesized via the quaternary ammonium reaction. Then, the synthesized octyl-QDED was blended with acrylonitrile butadiene styrene (ABS) through the melt extr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 52 publications
(67 reference statements)
0
4
0
Order By: Relevance
“…In particular, the use of antimicrobial composite material along with FFF specifically for bio-applications has been widely studied [ 44 , 45 ]. For instance, biodegradable polymers such polylactic acid- (PLA) based polymers are often used to develop filament that possess antibacterial properties using FFF as discussed by Bronstein et al [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, the use of antimicrobial composite material along with FFF specifically for bio-applications has been widely studied [ 44 , 45 ]. For instance, biodegradable polymers such polylactic acid- (PLA) based polymers are often used to develop filament that possess antibacterial properties using FFF as discussed by Bronstein et al [ 46 ].…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of the polymer composites are reinforcement type, content, and printing parameters. The printing parameters like layer height, raster angle, infill density, printing speed, infill pattern, and bed temperature [ 23,47–83 ] are extensively investigated by researchers to optimize the mechanical properties, as shown in Table 2.…”
Section: Mechanical Properties Of Am Compositesmentioning
confidence: 99%
“…This decreasing trend was found due to the introduction of the fine reinforcement particles, which decreased interactions among the chain of polymers. [ 55 ] The addition of carbon nanotubes in PEEK showed varying results for the ultimate tensile strength and shear strength; with the increase in the weight percentage addition of reinforcement, there was an increase in the ultimate tensile strength while opposing to that there was a decrease in shear strength, as it depends on the surface characteristics such as surface tension, adhesion, and wettability for different reinforcement conditions. [ 79 ] Ultimate tensile strength, flexural strength, and Young's modulus tests were conducted on the samples printed from a TiO 2 ‐reinforced ABS, which revealed that the addition of TiO 2 increased the properties by 12%–29%.…”
Section: Mechanical Properties Of Am Compositesmentioning
confidence: 99%
“…The same biofunctionalization treatments in in vitro tests showed that porous implants with an increased surface area release a significantly higher amount of antimicrobial agent and have an increased inhibition zone size as compared to solid implants with the same dimensions [46]. The difference is that for AM polymer implants, which are manufactured by fused deposition modeling (FDM) or stereolithography (SLA), antimicrobial agents such as antibiotics [47,48], quaternary ammonium salts [49,50], chitosan [51], and antimicrobial metal particles [52] are usually added to the raw material during the manufacturing stage to facilitate the generation of bactericidal surfaces. At present, there are very few studies on the direct preparation of antimicrobial Ti implants using AM.…”
Section: Introductionmentioning
confidence: 99%